Control Techniques and Open-Circuit Fault Analysis on Single Phase T Inverter - Võ Quốc Thái,; Đào Văn Tâm,; Lê Hiển Vinh,; Nguyễn Phước Lộc,; Bùi Thanh Hiếu, (Journal of Technical Education Science, 2025)
This article presents a pulse width modulation method to control a T configuration single-phase inverter (T-1F) when encountering an open circuit fault in the T branch. Multi-level inverters are often widely used in medium and large power conversion systems thanks to outstanding advantages compared to conventional inverters. In addition to reducing high voltage levels applied to components, multi-level inverters also have the ability to reduce harmonic indexes to a lower level thanks to the pulse width control method. Among the popular multi-level inverter configurations such as cascade inverters and H-bridge inverters, T configuration inverters are being researched with many advantages such as harmonic reduction (THD) and common-mode voltage reduction ( CMV). This article investigates the quality of voltage, current and loss harmonics on semiconductor components of the T-1F inverter. The proposed pulse width modulation method (T-Pr) is based on the opposing operating principle of IGBT switches on the T-1F inverter. Analysis results will be evaluated through simulation using MATLAB/SIMULINK software. Simulation results of the proposed pulse width modulation method for the T-1F inverter will be compared with conventional pulse width control techniques. In addition, to evaluate the loss of the T-1F inverter, PLECS software is used. Evaluation of the obtained results confirms the advantages of the proposed T-Pr method on the T-1F inverter configuration.